The generalized triple difference of \(χ^3\) sequence spaces - Subramanian, N.; Esi, Ayhan (Global Journal of Mathematical Analysis, 2015)
In this paper we define some new sequence spaces and give some topologicalÂ properties of the sequence spaces \(χ^3( Δ_v^m,s, p)\) and \(Λ^3( Δ_v^m,s, p) \) and investigate someÂ inclusion relations.